LIRIK LAGU SEMUA AKU DIRAYAKAN KARYA NADIN HAMIZAH - Gusnatul, Laila (JURNAL SKRIPTA, 2024)
Songs are literary works that express certain meanings through the words placed in the text. The meaning of a song is explained by its lyrics, which can also express the author's feelings or opinions about something. The aim of this research is to analyze the lyrics of Nadine Hamizah's song "All I'm Celebrated" and to clarify the relationship between lyrical and non-lyrical elements. The critical discourse analysis (CDA) model approach by Teun A. Van Dijk is used as an analytical tool. Qualitative methods were used in this research. Library research methods will be used for data collection. Research data is available in the form of lyric fragments. The source of research data is the lyrics of the song "All I Celebrate" by Nadin Hamizah. From the results of my research, I found that there is a macro structure consisting of the meaning of the lyrics, and a super structure consisting of intro, verse, bridge, chorus, etc. Then there is the micro structure in the form of semantic, syntactic and rhetorical studies.